(3GdJUQja def YLR Yf GdJCdja aj GdWHs - (3GdRgQGhqj GdCfOdSj, CHh GdbGSe, Nda Hf YHGS, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdebGdI GdKGefI hGdYTQhf aj GUdGM GdCOhdI ; bGd GdeDda CLeYJ gPG GdcJGH GdYXje GdaGFOI GdPj SejJg HcJGH GdJUQja aj GdCOhjI GdeQcHI hCcedJ LejY ebGdGJg Ydi MSH eQZhHj hLOJ aj cKjQ ef fSN GdCOhjI s
(3BNQgG (B:s
(3GdebGdI GdKdGKhf aj Yed GdjO ef GdLHQ hGdcSQ hGdNdY GdHGH GdKGdK aj GdLHQ GdaUd GdNGeS hGdKdGKhf aj CfhGY Gdac GdPj jchf eY LQM Ch eY cSQ Ch eYgeG LejYG eYG cedJ GdebGdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B2\310s
(3cTa GdXfhf (B1\411s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs